2017
DOI: 10.1186/s12879-017-2756-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mycobacterium tuberculosis viability in OMNIgene-SPUTUM reagent upon multi-day transport at ambient temperature

Abstract: BackgroundMaintaining the quality of clinical specimens for tuberculosis (TB) testing is a major challenge in many high TB burden-limited resources countries. Sample referral systems in low and middle income countries are often weak and the maintenance of the cold-chain challenging and very costly for TB programs. The development of transport media allowing the preservation of samples without refrigeration is critical for increasing access to TB diagnostic services and for reducing the costs related to testing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 8 publications
0
12
1
Order By: Relevance
“…There was only one contaminant on untreated samples at day 0. Previous studies have shown that OM-S-treated samples have a lower contamination rate than untreated counterparts (10,(12)(13)(14)(15)23). In our study, only one contaminant in the untreated group may not explain much about the contribution of OM-S in reducing contamination compared to standard decontamination.…”
Section: Discussioncontrasting
confidence: 73%
See 3 more Smart Citations
“…There was only one contaminant on untreated samples at day 0. Previous studies have shown that OM-S-treated samples have a lower contamination rate than untreated counterparts (10,(12)(13)(14)(15)23). In our study, only one contaminant in the untreated group may not explain much about the contribution of OM-S in reducing contamination compared to standard decontamination.…”
Section: Discussioncontrasting
confidence: 73%
“…Finally, we observed a substantial delay in days to positivity between untreated and OM-S-treated samples at both time points. Previous studies have also noted delayed culture growth in samples treated with OM-S (13,15,21,22). This raises further concerns about the utility of OM-S in its current procedure and the compatibility with MGIT cultures.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…8 The mycobacterial cell wall with its thick and relatively impermeable layer of mycolic acid has 9 unique characteristics. The complexity of the cell wall represents a challenge to the organism, 10 requiring specialized mechanisms to allow cell division to occur and resulting in prolonged 11 generation times compared to gram-positive or -negative bacteria. 4 Respiratory samples are 12 therefore specially treated, a process called 'decontamination' before inoculation and incubation 13 of broth and solid media.…”
Section: Introductionmentioning
confidence: 99%